Pengisian Kekosongan Kepala Daerah Sebelum Pemilihan Kepala Daerah Serentak - Said, Mochamad; Junaidi, Muhammad; Sudarmanto, Kukuh; Sofyan, Syafran (Universitas Semarang, 2024)
The aim of this research is (1) to analyze the regulatory mechanism for filling vacancies for Regional Heads whose terms of office expire before 2024. (2) To analyze the obstacles and solutions for filling vacancies for regional heads in leading regional government administration according to applicable laws and regulations. This research method is a normative juridical method with analytical descriptive specifications. The data used is secondary data in the form of primary, secondary, and tertiary legal materials, while the technique for collecting legal materials uses library studies and documentation studies which are then analyzed qualitatively. The research results show that the legal basis for filling vacancies for Regional Heads whose term of office expires before 2024 is Article 201 paragraphs (9), (10), and (11) of Law Number 10 of 2016. However, this law only regulates to the extent the qualifications of the officials appointed, while the procedures or mechanisms for appointing officials to fill the vacancies of Regional Heads more comprehensively are not accommodated. The obstacle to filling vacancies for regional heads is the absence of definite legal regulations regarding the limits of the authority of regional heads. The solution is that the government should issue implementing regulations from Article 201 of Law Number 10 of 2016 which contain procedures for filling vacancies in regional head positions. The problem is that there are objections to the appointment of Regional Head Officials, the solution is to implement a system for determining Regional Head Officials through voting by Provincial DPRD members to elect Regional Head Officials (Pj) after passing selection by the Ministry of Home Affairs and Regional Government. vacancies of Regional Heads more comprehensively are not accommodated. The obstacle to filling vacancies for regional heads is the absence of definite legal regulations regarding the limits of the authority of regional heads. The solution is that the government should issue implementing regulations from Article 201 of Law Number 10 of 2016 which contain procedures for filling vacancies in regional head positions. The problem is that there are objections to the appointment of Regional Head Officials, the solution is to implement a system for determining Regional Head Officials through voting by Provincial DPRD members to elect Regional Head Officials (Pj) after passing selection by the Ministry of Home Affairs and Regional Government. Keywords: Emptiness; Position; Regional Head Officials; Regional elections Abstrak Tujuan penelitian ini untuk menganalisis pengaturan mekanisme pengisian dan kendala solusinya pengisian kekosogan kepala daerah yang habis masa jabatannya sebelum tahun 2024. Metode penelitian ini adalah metode yuridis normatif dengan spesifikasi deskriptif analitis. Hasil penelitian menunjukkan bahwa dasar hukum pengisian kekosongan Kepala Daerah yang habis masa jabatannya sebelum tahun 2024 adalah Pasal 201 ayat (9), (10) dan (11) Undang-Undang Nomor 10 Tahun 2016. Akan tetapi, undang-undang ini hanya mengatur sebatas kualifikasi penjabat yang diangkat, sedangkan prosedur atau mekanisme pengangkatan pejabat untuk mengisi kekosongan Kepala Daerah secara lebih komprehensif tidak diakomodir. Kendala atas pengisian kekosongan kepala daerah adalah tidak adanya aturan hukum pasti tentang batasan kewenangan pejabat Kepala Daerah. Solusinya yaitu pemerintah sudah seharusnya menerbitkan aturan pelaksana dari Pasal 201 Undang-Undang Nomor 10 Tahun 2016 yang berisi tata cara mengisi kekosongan jabatan kepala daerah. Kendala adanya adanya penolakan-penolakan atas Penunjukan Pejabat Kepala Daerah maka solusinya yaitu menerapkan sistem penetapan Pejabat Kepala Daerah melalui pemungutan Suara anggota DPRD Provinsi untuk memilih pejabat (Pj) Kepala Daerah setelah lolos diseleksi oleh Kemendagri dan Pemerintah Daerah.